Politeness Strategies in Conversations about Transgender Perspectives: A Gender-Based Analysis - Male, Hendrikus; Sbastian, Daniel (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This study explores politeness strategies in conversations about transgender perspectives, using Brown and Levinson's (1987) framework. The research employed a qualitative method, analyzing recorded conversations between male and female participants discussing transgender issues from social and religious perspectives. The analysis identifies four main strategies: positive politeness, negative politeness, bald-on record, and off-record. Positive politeness was the most frequently used strategy, with male speakers employing it 14 times and female speakers 7 times, primarily through agreement, repetition, and joking. Negative politeness strategies appeared 10 times, equally distributed between genders, using indirectness and questions. Bald-on record strategies were used 14 times, mostly by female speakers, indicating their tendency for direct communication. The off-record strategy was minimally used, occurring only once by a male speaker. The study finds that participants' close relationships and shared knowledge facilitated the frequent use of positive politeness and bald-on record strategies. Notably, male speakers were more polite, often using positive politeness, while female speakers were more direct and explicit, especially on sensitive topics. This research highlights the influence of social dynamics and cultural norms on politeness strategies in discussions about transgender issues.Â